Direct development or endotrophic tadpole? Morphological aspects of the early ontogeny of the plump toad Osornophryne occidentalis (Anura: Bufonidae). (4th April 2023) - Romero‐Carvajal, Andrés; Negrete, Leonardo; Salazar‐Nicholls, María J.; Vizuete, Karla; Debut, Alexis; Dias, Pedro H.; Vera Candioti, Florencia
Abstract: Andean Toads of the genus Osornophryne are suspected to have direct development on the basis of clutch and egg features. In this work, we describe the morphology of Osornophryne occidentalis embryos from a nest collected in the field. Several traits are similar to those reported in brachycephaloid Eleutherodactylus coqui and other direct‐developing lineages. These include the pattern of formation of the body wall and the absence of oral and buccopharyngeal structures. Other features indicate the retention of ancestral larval characters. The development of forelimbs occurs in part within the operculum as in species with biphasic ontogeny; this has been reported in other direct‐developing species, and is similar to what is described in African viviparous bufonids. This salient feature, along with the long, low‐finned tail and the long and folded intestine early differentiated, gives these embryos a rather tadpole‐like appearance. Our data confirm that development in O. occidentalis occurs within terrestrial eggs until advanced stages, and this would satisfy current definitions of direct development. At the same time, morphological differences regarding other species with comparable breeding reinforce interpretations about the wide anatomical and ontogenetic variations associated with endotrophic nutrition. Abstract : Direct development in Andean toads Osornophryne occidentalis, the single direct‐developing bufonid embryos described to date, retains tadpole‐like features such as forelimbs concealed by the operculum, long tail, and long, folded, and early differentiated gut. This represents a markedly different pattern regarding the well‐known direct‐developing embryos of Eleutherodactylus coqui and contributes to the discussion of anatomical and ontogenetic variations in frogs with endotrophic nutrition.